Lessons amid the Rubble: An Introduction to Post-Disaster Engineering and Ethics - Pfatteicher, Sarah K. A (Johns Hopkins Introductory Studies in the History of Technology, 2010)
The aftermath of September 11, 2001, brought the subject of engineering-failure forensics to public attention as had no previous catastrophe. In keeping with the engineering profession's long tradition of building a positive future out of disasters, Lessons amid the Rubble uses the collapse of the World Trade Center towers to explore the nature and future of engineering education in the United States. Sarah K. A. Pfatteicher draws on historical and current practice in engineering design, construction, and curricula to discuss how engineers should conceive, organize, and execute a search for the reasons behind the failure of man-made structures. Her survey traces the analytical journey engineers take after a disaster and discusses the technical, social, and moral implications of their work. After providing an overview of the investigations into the collapse of the Twin Towers, Pfatteicher explores six related events to reveal deceptively simple lessons about the engineering enterprise, each of which embodies an ethical dilemma at the heart of the profession. In tying these themes together, Pfatteicher highlights issues of professionalism and professional identity infused in engineering education and encourages an explicit, direct conversation about their meaning. Sophisticated and engagingly written, this volume combines history, engineering, ethics, and philosophy to provoke a deep discussion about the symbolic meaning of buildings and other structures and the nature of engineering.